Sulfur(IV)-mediated carbon-carbon bond formation - Dean, William Michael (2016)
This thesis details the development of methods for and application of the synthesis of carbon carbon bonds using organic sulfur(IV) chemistry. More specifically, the formation of C(sp2) C(sp3) and C(sp3) C(sp3) bonds is explored in detail. The necessity for this research stems from a correlation between a high proportion of sp3 centres in drug candidates, and their success in clinical trials. By facilitating the synthesis of drug candidates with higher fractions of sp3 hybridised carbon atoms, it is hoped that the rate of candidates proceeding through clinical trials may increase. The first topic addressed is the ligand coupling reactions of sulfoxides. In such reactions, the treatment of appropriately substituted sulfoxides with organometallic reagents forms C(sp2) C(sp3) coupling products via σ sulfurane intermediates. These reactions have the ability to excel where transition metal catalysed cross couplings fail; in the coupling of electron deficient (hetero)aromatic groups and alkyl groups. Very few reports have been published detailing the scope and utility of this reaction. The application of this methodology to the synthesis of diarylmethanes is explored in detail. Diarylmethanes are designated as privileged structures for the presence of these moieties in a vast array of diversely functional drug products. Investigation of the scope of the ligand coupling reaction allows for the elucidation of (hetero)aromatic moieties which can undergo this reaction. The depth of analysis in which the scope of benzylic substituents is studied allowed for the elucidation of previously unreported trends, which have been assigned to steric and electronic characteristics of the σ sulfurane intermediates. This knowledge gained is applied to the synthesis of both enantiomerically enriched diarylmethanes and well known drug products. Further exploration of the scope of ligand coupling reactions focusses on the coupling of α functionalised alkyl groups. Remarkable success is found in this completely unexplored area. Benzylic ethers, carbamates and halides are synthesised through a combination of inter molecular and intra molecular ligand coupling reactions. It is proposed that these reactions would be suitable for use in the synthesis of natural products to prove their utility. A newly-discovered sulfoxide homologation is detailed, which occurs upon reaction of sulfenate by products with the aforementioned benzylic halides, both synthesised by a ligand coupling reaction. This is particularly interesting since a similar homologated sulfoxide is found in the substructure of omeprazole, a blockbuster proton pump inhibitor. The second topic addressed is the synthesis of (±)-TAN1251A. The envisaged route proceeds through a novel palladium catalysed [3+2] cycloaddition of sulfinimines, forming methylene pyrrolidines. Previous work focussed on the use of this methodology to produce a diamine, mono-protected as a sulfonamide. A key aspect of the research presented in this thesis is the formation of the C ring of the spiro fused 1,4 diazabicyclo[3.2.1]octane moiety. Initial investigations focus on the synthesis of a pyruvic acid fragment to react with the aforementioned diamine. This concept is developed into the use of pyruvic acid synthetic equivalents: azlactones. A late stage intermediate is produced, however formation of the C ring from this intermediate is not observed. Synthesis is hampered by the deprotection of the sulfonamide, which forms several by-products under the strongly acidic conditions required. A revised retrosynthesis proposes that early deprotection of the diamine sulfonamide would prevent complications. The use of a simplified fragment to facilitate C ring formation is devised, comprising of an α-haloketone. Synthesis of the unprotected diamine is accelerated by serendipity, where a reductive amination also effects the elimination of a sulfinyl group. Formation of an α haloketone fragment is found to be troublesome, however synthesis via the natural product chavicol provides the required functionality. A wide variety of conditions are examined to effect the combination of these fragments. While coupling of the fragments is successful in providing another late-stage intermediate of (±) TAN1251A, formation of the desired C ring is not achieved. Finally, the potential to effect an enantioselective synthesis of (±)-TAN1251A is confirmed using a chiral sulfinamide to direct diastereoselective ketone reduction.